The Role of Plant Essential Oils in Poultry Disease Prevention - Josiah, E. P.; Ashimi, A. A.; Akande, K.E.; Adebayo, R.A. (ADAN JOURNAL OF AGRICULTURE, 2026)
Plant essential oils (PEOs) have gained prominence as natural alternatives for disease prevention in poultry, driven by concerns over antibiotic resistance and consumer demand for antibiotic-free products. This review evaluates studies on the antimicrobial, antioxidant, and immunomodulatory properties of essential oils, highlighting their role in controlling poultry diseases such as Aspergillosis. Essential oils exhibit broad-spectrum antimicrobial activity, enhance immune function, and improve feed efficiency, contributing to poultry health and productivity. Key bioactive compounds, including phenols, aldehydes, and terpenes, disrupt pathogenic bacteria, inhibit fungal growth, and promote gut microbiota balance. While research supports their efficacy, challenges remain in standardization, optimal dosage, and regulatory approval. Future studies should focus on refining formulations and conducting large-scale trials to validate their application in commercial poultry farming. Essential oils represent a promising, sustainable alternative to synthetic antibiotics, offering potential benefits for animal health and food safety